Director’s interpretation of Kazakh dance: development trajectories in the perspective of creativity - Kussanova, Anipa; Tleubayeva, Balzhan; Nikolayeva, Lyudmila; Shankibayeva, Aliya (Creativity Studies, 2021)
The study investigates the director’s interpretations of Kazakh dance in the perspective of creativity on the example of works dated the last quarter of the 20th – early 21st century to determine the choreography’s development vectors with taking into account the aspect of creativity. This research is based on the small and large dance performances analysis. The study relevance lies in the fact that it can become a tool for determining the expression level of the national aspect in Kazakh dance art. The results of the study show the role of creativity in the dance education and its ffectiveness in the development of Kazakh dance art. This tool is necessary for the choreographer’s worldview theoretical analysis and his/her dance interpretation, for the Kazakh choreography subsequent enrichment, and preservation of Kazakh historical identity.